Significant Improvement of Switching Characteristics in a 1.2‐kV SiC SWITCH‐MOS by the Application of Kelvin Source Connection. Issue 2 (17th October 2022) - Matsui, Kevin; Tawara, Takeshi; Harada, Shinsuke; Tanaka, So; Sato, Hiroshi; Yano, Hiroshi; Iwamuro, Noriyuki
Abstract : Here we show, for the first time, a significant improvement of switching characteristics in a 1.2‐kV SiC Schottky barrier diode‐wall integrated trench MOSFET (SWITCH‐MOS) by the application of a Kelvin source (KS) connection. Turn‐on loss ( E on ) was greatly reduced, with superior E on ‐d V DS /d t trade‐off characteristics at a moderate d V DS /d t value of about 10 kV/μs, because the SWITCH‐MOS with KS achieves a more suppressed peak reverse recovery current in embedded Schottky barrier diodes even at a higher d I D /d t during the turn‐on operation than a state‐of‐the‐art SiC trench MOSFET with KS. This feature is a peculiarity of the SWITCH‐MOS when the KS connection is applied. Notably, measured and calculated results confirmed that the SWITCH‐MOS with KS had less dissipated turn‐off loss, especially in a second half of turn‐off regions (Region 2), than the SWITCH‐MOS w/o KS. However, owing to a higher negative turn‐off d I D /d t, the MOSFET with KS has a larger drain surge voltage. With an optimum gate resistance, the SWITCH‐MOS with KS has 8% less total switching loss than a SWITCH‐MOS without KS, and 29% less than a state‐of‐the‐art SiC trench MOSFET with KS, while keeping a moderately low d V DS /d t of 10 kV/μs and suppressing a drain peak voltage of <720 V. © 2022 Institute of Electrical Engineers of Japan. Published by Wiley Periodicals LLC.